Stock returns and volatility: Pricing the short-run and long-run components of market risk - Tobias Adrian; Joshua Rosenberg (Federal Reserve Bank of New York, 2006)
We explore the cross-sectional pricing of volatility risk by decomposing equity market volatility into short- and long-run components. Our finding that prices of risk are negative and significant for both volatility components implies that investors pay for insurance against increases in volatility, even if those increases have little persistence. The short-run component captures market skewness risk, which we interpret as a measure of the tightness of financial constraints. The long-run component relates closely to business cycle risk. Furthermore, a three-factor pricing model with the market return and the two volatility components compares favorably to benchmark models.
Keywords: G10; G12; 330; asset pricing; stochastic volatility; cross section of returns; Capital Asset Pricing Model; Volatilität; Stochastischer Prozess; Kapitalertrag; ARCH-Modell; Theorie